Implicit location encoding via stored representations of familiar objects: neuropsychological evidence. - Shalev, L; Humphreys, G (2002)
We report data on the visual localisation ability of a patient with Balint's syndrome, GK. We show that, with relatively long exposures of displays, GK is better able to judge the spatial relations between separate objects (a "between-object judgement") than the spatial relations between a part and a whole object (a "within-object judgement") (Experiments 1-3). This dissociation occurred even when the same stimulus was used for both judgements, and the task instructions biased GK to parse the stimulus as either a single or as two separate objects (Experiments 2 and 6). However, when he could use a stored representation to make a within-object judgement, then performance was better than on a comparable spatial judgement of the relations between two separate objects (Experiments 4-7). The data demonstrate that stored representations of objects can support the spatial coding of parts to perceptual wholes. In the absence of stored representations, part-whole relations must be explicitly coded by attention, a process that is impaired in this patient.